The Intersection of AI and Science Education in Indonesia: A Path Forward - Harianti, H.; Kadarohman, A.; Anwar, S. (Universitas Negeri Yogyakarta, 2025)
ChatGPT's launch by the end of 2022 caused significant global disruption, particularly in education. ChatGPT acts as a computer capable of answering inquiries in multiple languages. The introduction of ChatGPT highlights the inevitable evolution of AI technology. Artificial intelligence (AI) is a rapidly emerging technical phenomenon and leading technology capable of functioning similarly to human intelligence. The study reviewed the literature semi-systematically. This approach searched for and overviewed the research area and the progress made. The first phase of this research was to formulate the research questions. The keywords were AI and science education. It was found that there are four categories for AI in educational institutions: University/ School Policies, Curriculum and Course Development, Pedagogical Innovations, and Professional Development with distance learning. The development of AI technology is inevitable in education. AI technology is not a threat if it can be integrated properly. This technology also applies to science education in Indonesia. Science education in Indonesia is often highlighted based on PISA results that do not meet global standards, so the existence of AI tools is an innovation in learning.